Kampen om arbejderne - arbejdsbegrebets politiske historie 1750-2015 - Bech Vilstrup, Margit (Slagmark - Tidsskrift for idéhistorie, 2018)
THE STRUGGLE FOR THE WORKERS - POLITICAL CONCEPTUALIZATIONS OF ’THE WORKER’, 1750-2015 Although ‘the worker’ has been one of the key concepts in political language since the second half of the 19th century only few studies have been made of the historical shifts in its definition and semantic demarcation. Inspired by present day semantic shifts in the meaning and use of ‘the worker’ in Danish political debate, this article examines the long history of the politicization of the concept. With inspiration from Reinhart Kosellecks Begrieffsgeschichte, the article analyzes how ‘the worker’ functions as both an indicator of and a factor in the creation of ‘the modern’. From being a concept used purely as a descriptive category for the wageworker in manual production in the pre-1790-era it changes into a category defining the workers as a social group with a revolutionary potential. The article argues that the concept plays a key role in political parties’ different strategies of mobilization and legitimization, and that since the 1970s a definitive change can be identified. A change that embodies what Francois Hartog has described as a transition from the future-oriented to the presentist regime.